Teaching evolution to psychiatrists in Venezuela: comparison with medical students and other medical specialists: a pilot study - Baptista, Trino; Aldana, Elis; Angeles, Felix; Delgado, Heidy (Canadian Medical Education Journal, 2012)
Introduction: The teaching of evolution theory (ET) in medical programs has received scant attention in the literature. In this report, we first describe the main applications of ET in medicine. Second, we present the evaluation of an interactive seminar on ET given to groups of medical students, psychiatrists, and other medical specialists. Methods: A two-hour, four-module, interactive seminar was conducted with separate groups of 27 psychiatrists, 15 family doctors, 18 neurologists, 13 physiatrists, 12 internists, and 24 sixth-year medical students without formal training in ET. Their knowledge of ET before and after the seminar was rated on a validated analogical scale (0-12). In addition, the perceived relevance of the information for the participants’ professional activity was assessed. Results: Score averages and medians before the seminar were below 6, suggesting low to moderate knowledge. The students' scores did not differ significantly from those of the physicians except on the Hominization item, where they scored lower than the physicians (p = 0.02). The psychiatrists’ scores did not differ from those of the other groups before the seminar, but after the seminar the increase in their scores on a number of items was significantly smaller than that of the other groups. While all groups scored 10 or more when assessing the relevance of the information, the psychiatrists had the lowest score (p = 0.024). Discussion: The results show the adequacy of short programs to enhance knowledge on ET. This may assist medical educators to develop comprehensive and compulsory courses. Future studies must explore whether psychiatrists are relatively reluctant or ambivalent to accept evolution concepts and proposals.